OP0021-PARE Patients Become Political - How to Support Patients' Involvement in Guideline Work Groups and the Joint Federal Committee of Physicians and Health Insurance Companies (G-BA). (10th June 2014) - Sander, C.
Abstract : Background: For a long time, health care professionals and insurance companies alone knew what is best for the patient. But a change of mind-set in politics and in society at large led to the Statutory Health Insurance Modernisation Act in Germany in 2004. It states, that relevant organisations which represent the interests of patients and self-help groups of chronically ill and disabled people have to be involved in questions concerning health issues and health care. Patient representatives (PR) of the Deutsche Rheuma-Liga participate in guideline work and political bodies of the health care system. They start out as active and dedicated patients who want to bring the patient perspective to the table. However, many come from non-healthcare related professions and have to face professionals of the health care system and insurance companies. Objectives: Full time staff from the Deutsche Rheuma-Liga supports and will support patients with rheumatic diseases in all aspects of their work as PRs in healthcare related political committees. Methods: For members who are interested in working as PR or who already work as PR, the Deutsche Rheuma-Liga – developed a "work description" including a brief background information about the political structures, qualifications that are good to have, and necessary requirements to fulfil the task – holds introductory work-shops to prepare new representatives – holds meetings where representatives can exchange their experiences – supports representatives with literature research and information input – if possible, a staff member accompanies new representatives to their first meeting – is available for questions related to any part of the work – informs about training courses from other institutions, e.g. G-BA. Results: Deutsche Rheuma-Liga supports PRs who participate in a number of different political committees and was able to win new people who want to influence the health care system in favour of the patients. However, new ways have to be found to include young people with rheumatic diseases who have less time for volunteer work. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4387